A arte na educação escolar: entre concepções e práticas - Moreira, Ana Marcia Akaui (2015)
There is almost a consensus among Brazilian researchers, that the teaching of Arts in Brazil was transformed by the Triangular Approach, introduced by Ana Mae Barbosa, which led to a new paradigm of work with arts in Education. Thus, supporting the central idea of the development and learning of Art in Dewey, Read, Eisner, Fischer and Arheim, this study aims to investigate how Art teachers, who adopt this approach, understand and build their practices in classroom. A qualitative approach, supported by Bodgan and Bicken, used for data collection, questionnaires and interviews with five Art teachers, experts, and who develop their work in the Junior High School at public schools in Baixada Santista. The organization of work and data analysis was guided in Hermeneutics-dialectic described by Minayo, with the operational support of Content Analysis described by Bardin and Franco. This research seems to show that teachers who use the Triangular Approach, although attempting to develop this proposal, conscious or not, are in a working condition weakened due to the absence of a specific, adequate and continuous education, because they feel at the margin of learning in school education. This work contributed to show how important is to work with Art in the schools and how the school can learn from this discipline.